The Paradox of Public Service Innovation amid Regional Autonomy in Indonesia - R. Slamet Santoso; Hardi Warsono; Retno Sunu Astuti; Ida Hayu Dwimawanti (JURNAL ILMU SOSIAL, 2023)
Law No. 23/2014 on the Local Government aims at fostering local governments in the country to nurture a culture of innovation to improve the quality of public services. This research attempts to discover paradoxes in the Surakarta City Government related to regulations governing local governments in Indonesia in developing public service innovation. This study uses a qualitative methodology with descriptive analysis related to the paradoxical evidence of public service innovation capacity in the Surakarta City government. Data were collected through in-depth interviews, observations, and literature studies of reputable journals. Furthermore, interviews were conducted with resource persons, from top management leaders to innovation actors, with a total of ten people. We utilised the analysis framework of Public Sector Innovation Capacity Management by Kim and Lee to analyse the results. We used SWOT analysis to devise a public service innovation capacity management strategy in Surakarta City. The results prove that the Surakarta City government has different characteristics in developing public service innovation. However, there is a paradox, which is a contradiction in the course of the local government in general. This paradox is evident in two main phenomena. First, there were no particular government regulations. Second, regional apparatus organisations (OPD) practice less collaborative mechanisms. By contrast, we found that entrenched innovation DNA and an external driver of innovation support the creation of public service innovations in the Surakarta City Government.